Conical waveguide design for propagating light to a single fiber and its indoor characterization methodology - Chapa-Garcia, Ricardo; Toral-Acosta, Daniel; Selvas-Aguilar, Romeo; López-Diaz, Juan Luis; Enriquez-Gomez, Luis Fernando (International Journal of Innovative Research and Scientific Studies, 2025)
This study introduces a novel optical setup and methodology to increase the effective area of a multimode optical fiber (MMF) using a low-cost, 3D-printed conical waveguide (CW). Designed to simplify solar collection systems with Fresnel lenses (FL) and optical fibers, the setup efficiently couples light into a single silica MMF. For this, an indoor characterization method assesses transmission efficiency, verifying in advance its suitability for outdoor use while minimizing sun exposure risks for the people conducting the experiments. A laser flashlight provides a collimated light source with approximately 2° divergence for experiments. Geometric analysis and ray-tracing simulations validate the CW design, highlighting the importance of a low FL numerical aperture (NA). By reducing the FL’s NA to 0.11 using masks, a maximum CW’s transmittance of 34.7% and a net system efficiency of 17% are achieved. Key advantages include simplified assembly, avoiding the complexities of fiber bundle manufacturing, low optical attenuation over tens of meters, and safe indoor characterization. This approach presents a solution for compact photonic energy transport systems and provides a reference framework for identifying improvements to the collection system. The findings of this study are intended for use in a sunlight collector device for indoor lighting.